«Одзакарпеты» из Гадрута - Аванесян, Лилия (Институт языкознания РАН)
В фондах Музея истории Армении хранятся безворсовые ковры-карпеты XIX века со стилизованными изображениями Змея – так называемые «Одзакарпеты». Эти шерстяные карпеты вытканы в сложной технике «косой обкрутки нити». В XVII веке подобные безворсовые карпеты начали изготовлять в городах Малой Азии – Себастии и Зиле. Mестом создания экспонатов представленных в Музее истории Армении являются Арцах–Сюник, Нахиджеван, Васпуракан. The History Museum of Armenia keeps lint-free carpets with large stylized images of the Dragon Snake from Artsakh, Syunik, Sebastia. Woolen carpets are woven by master carpet weavers using the complex technique of oblique wrapping. In the XVIIth century, such lint-free carpets began to be made in the cities of Asia Minor Sebastia and Zile. However, the places of origin of these valuable products are Artsakh-Syunik, Nakhijevan, Vaspurakan. The Armenian historian Arshak Alpoyachyan, based on the study of historical documents, testifies that in the middle of the XVIth century, during military campaigns in the Asia Minor, a large number of Armenians were driven away from the eastern provinces of Armenia – from Nakhijevan, Artsakh, Vaspurakan and Yerevan. Among the people driven to the cities of Sebastia, Tokat, Zile and others, there were many artisans and carpet weavers. And the Hungarian art historian Károly Gombos writes that the carpets with images of dragons (vishaps) began to be made in the XIIth–XVIth centuries, and Artsakh was the place of the their origin of “Vishapagorgs” (dragon-carpets).
Keywords: Фольклористика; Этнография; Ковроткачество